A metal plate-free bipolar solid-state battery and a dry method for preparing the same
Patent Information
- Application Number
- CN202611102531.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]然而,双极型电池采用金属板的结构设计存在以下问题:(1)金属双极板密度大(尤其是铜箔和不锈钢箔),其重量通常占电池堆总重量的15%至25%
(1)显著减重:取消金属双极板可降低电池总重量20%以上,质量能量密度提升20-30%;(2)界面阻抗降低:通过热压工艺使上下两层自支撑膜深度融合,导电网络在界面处连续贯通,实测界面电阻低于传统金属/电极界面;(3)无腐蚀风险:完全取消金属板,根除了金属电化学腐蚀问题,提升了电池循环寿命;(4)无离子串扰:采用固态电解质代替液态电解液,有效解决双极性电池内部串联时电解液离子串扰的问题。
Smart Images

Figure CN123018073A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a metal-plate-free bipolar solid-state battery and its dry preparation method. Background Technology
[0002] A bipolar battery is a type of battery that uses a bipolar plate structure. It typically employs metal bipolar plates (such as copper foil, aluminum foil, or stainless steel foil) as current collectors and series connectors. This involves coating one side of the metal plate with a positive electrode material and the other side with a negative electrode material, then stacking them to form a series structure. By connecting multiple individual cells in series, it can achieve high voltage output within a single physical structure, significantly improving the volumetric energy density and gravimetric energy density of the battery pack. Therefore, it has significant application prospects in fields with stringent requirements for energy density and lightweight design, such as aerospace, electric vehicles, and military equipment.
[0003] However, the structure design of bipolar batteries using metal plates has the following problems: (1) The density of metal bipolar plates is high (especially copper foil and stainless steel foil), and their weight usually accounts for 15% to 25% of the total weight of the battery stack. In the context of increasingly stringent requirements for lightweight application scenarios, this weight ratio has become a key bottleneck restricting the further improvement of the overall mass energy density of the battery stack; (2) The metal and electrode materials are dissimilar materials in contact. On the one hand, the physical contact between the two inevitably introduces contact resistance, which increases the internal friction of the battery stack; on the other hand, there is a significant mismatch in the coefficient of thermal expansion between the metal and the electrode active material. During the periodic temperature fluctuations generated by charge and discharge cycles, alternating thermal stress will accumulate at the interface, which can easily lead to failure of the contact interface in the long term, causing a sharp increase in the internal resistance of the battery stack; (3) Under high pressure or high temperature conditions, the metal current collector may be electrochemically corroded, leading to the degradation of battery life. Summary of the Invention
[0004] The present invention aims to provide a metal-plate-free bipolar solid-state battery and its dry preparation method, which eliminates the metal bipolar plate and maintains a novel bipolar battery structure with low interfacial resistance and good mechanical integrity.
[0005] To achieve the above objectives, the first aspect of this application provides the following technical solution: A metal-plate-free bipolar solid-state battery includes at least two composite stacks connected in series, each composite stack comprising a positive self-supporting membrane, a separator, and a negative self-supporting membrane stacked in series; in two adjacent composite stacks, the negative self-supporting membrane of the previous composite stack is in contact with the positive self-supporting membrane of the next composite stack.
[0006] The optimized thickness of the positive electrode self-supporting membrane is 50-150 μm, the thickness of the negative electrode self-supporting membrane is 40-120 μm, and the thickness of the separator is 10-50 μm.
[0007] In some embodiments, the raw materials, by mass parts, include 60-90 parts of positive electrode active material in the positive electrode self-supporting membrane and 60-90 parts of negative electrode active material in the negative electrode self-supporting membrane; and each of the positive electrode self-supporting membrane and the negative electrode self-supporting membrane further includes: 5-25 parts of solid electrolyte powder, 2-10 parts of conductive agent, and 1-8 parts of binder.
[0008] Furthermore, the raw materials, by weight, include 85-98 parts of solid electrolyte powder and 2-15 parts of binder in the diaphragm.
[0009] In some embodiments, The positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, and lithium iron phosphate; The negative electrode active material is selected from one or more of synthetic graphite, natural graphite, hard carbon, soft carbon, silicon-carbon composite material, lithium titanate, and lithium metal. The solid electrolyte powder is selected from one or more of oxide electrolytes, sulfide electrolytes, and polymer electrolytes.
[0010] Furthermore, the conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene; the binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, or polyimide.
[0011] A second aspect of this application provides a method for preparing a bipolar solid-state battery, comprising the following steps: S1. According to the above mass proportions, the raw materials are mixed separately and then rolled to form a positive electrode self-supporting membrane, a separator and a negative electrode self-supporting membrane of the target thickness. S2. The positive electrode self-supporting membrane, the separator and the negative electrode self-supporting membrane are stacked in sequence and hot-pressed to obtain a composite stack; at least two composite stacks are stacked and hot-pressed to obtain a fuel cell stack structure. S3. Place a positive electrode current collector above the top positive electrode self-supporting film of the stack structure, and place a negative electrode current collector below the bottom negative electrode self-supporting film. The whole package can be used to obtain a bipolar solid-state battery.
[0012] The optimized hot pressing temperature is 80~200 ℃ and the pressure is 10~200 MPa.
[0013] Furthermore, the mixing is carried out by air jet milling or high-energy ball milling; and the mixture is repeatedly rolled by a roller press under room temperature or heating conditions.
[0014] In some specific embodiments, the positive terminal subcurrent collector is an aluminum foil, and the negative terminal subcurrent collector is a copper foil.
[0015] Working principle of the invention: (1) The mechanism of this technical solution for "how to maintain the electronic path of adjacent units after the metal plate is removed" Traditional stacked batteries have an internal parallel structure, where each positive / negative electrode relies on a metal plate (current collector) to transfer electrons generated by oxidation-reduction to the external circuit. Bipolar batteries, on the other hand, have an internal series structure, where electrons from each cell only need to transfer along the electrode thickness direction to the next cell; the electron transport path between adjacent cells is only tens of micrometers. Therefore, the metal plate in traditional bipolar batteries is used to increase the contact area between the positive and negative electrode materials of adjacent cells, thereby improving electron transport efficiency. However, the metal / electrode interface is a physical contact between dissimilar materials, and the actual contact area between the metal and the electrode is only 10-20% of the apparent area, resulting in significant contact resistance. The technical solution of this application intercalates the positive and negative electrode films through thermo-pressing composite, and the binder and conductive agent fill the micropores, making the actual contact area approach the geometric area (100%). Electrons can be directly transported from the positive / negative electrode composite interface. The thermo-pressing composite method forms a continuous conductive network to replace the electron transport function of the metal plate, achieving the effect of "weight reduction without reducing conductivity." Therefore, by using this technical solution, not only will the electronic pathway be not disrupted after the metal plate is removed, but the electronic transmission efficiency at the interface will also be greatly improved.
[0016] (2) The mechanism of this technical solution for "maintaining the strength of the electrode structure without metal plate support" Traditional bipolar batteries employ a wet process, requiring the positive and negative electrode materials to be coated onto a metal plate. The structural stability of the entire battery stack depends on the support of this metal plate. This application utilizes a dry process to prepare self-supporting films for both positive and negative electrodes. A fiber network structure is formed through high-speed shearing of a dry binder, enabling interconnection between active particles. The self-supporting film prepared using this dry process exhibits excellent mechanical self-support, completely eliminating the structural dependence of the positive and negative electrodes on the metal plate.
[0017] The mechanism by which this technical solution solves the "ion crosstalk" problem lies in using a solid electrolyte instead of a liquid electrolyte. In liquid bipolar batteries, when the number of cells connected in series exceeds 3-4, the total voltage across the stack can reach 15-20V, far exceeding the electrochemical stability window of the liquid electrolyte. This leads to electrolyte decomposition and gas production, and electrolyte ions can crosstalk and migrate between adjacent cells, causing short circuits. In contrast, the solid electrolyte used in this application ensures that the electrolyte in each cell does not crosstalk with each other and only bears the voltage of that cell (3-4V), fundamentally eliminating short circuits between cells and electrolyte decomposition problems.
[0018] The beneficial effects of this invention are: (1) Significant weight reduction: Eliminating the metal bipolar plate can reduce the total weight of the battery by more than 20% and increase the mass energy density by 20-30%; (2) Reduced interface impedance: The hot pressing process allows the upper and lower self-supporting films to be deeply integrated, and the conductive network is continuously connected at the interface. The measured interface resistance is lower than that of the traditional metal / electrode interface; (3) No corrosion risk: The metal plate is completely eliminated, eliminating the problem of metal electrochemical corrosion and improving the battery cycle life; (4) No ion crosstalk: Solid electrolyte is used instead of liquid electrolyte, which effectively solves the problem of electrolyte ion crosstalk when the bipolar battery is connected in series. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of a bipolar solid-state battery. Figure 2 This is a schematic diagram of the structure of the composite laminate. Figure 3 This is a schematic diagram of a traditional bipolar battery with a metal plate. Figure 4 The specific energy test results are for the examples and comparative examples; Figure 5 The battery rate test results are for the examples and comparative examples. Detailed Implementation
[0020] The following detailed description illustrates the specific implementation method: Example 1: Fabrication of a metal-plate-free bipolar solid-state battery Preparation of the self-supporting cathode film: 80 parts of lithium cobalt oxide cathode material, 10 parts of LLZTO (lithium lanthanum zirconium tantalum oxide) solid electrolyte, 5 parts of conductive carbon black, and 5 parts of polytetrafluoroethylene were dry-mixed in a high-speed mixer for 10 minutes, and then treated twice by an air jet mill (pressure 0.6 MPa) to fiberize the binder. The fiberized mixture was repeatedly hot-pressed on a two-roll mill to obtain a final areal density of 3.2 g / 100 cm³. 2 A positive electrode self-supporting film with a thickness of 110 μm; Preparation of the self-supporting negative electrode film: 75 parts of graphite negative electrode material, 15 parts of LLZTO solid electrolyte, 5 parts of conductive carbon black, and 5 parts of polytetrafluoroethylene were dry-mixed in a high-speed mixer for 10 minutes, and then treated twice by an air jet mill (pressure 0.6 MPa) to fiberize the binder. The fiberized mixture was repeatedly hot-pressed on a two-roll mill to obtain a final density of 1.5 g / 100 cm³. 2 A self-supporting negative electrode film with a thickness of 120 μm.
[0021] Membrane preparation: 95 parts LLZTO and 5 parts polytetrafluoroethylene binder were dry-mixed in a high-speed mixer for 10 minutes, and then treated twice by an air jet mill (pressure 0.6 MPa) to fiberize the binder. The fiberized mixture was repeatedly hot-pressed on a twin-roll press to finally obtain a membrane with a thickness of 25 μm.
[0022] Thermopressing and encapsulation: Refer to Figure 2 The positive electrode membrane, electrolyte, and negative electrode membrane are stacked in sequence to form a composite stack, as shown in the reference. Figure 2 Four identical composite stacks are then stacked sequentially, without any metal plates between adjacent stacks. Only a 12 μm aluminum foil is placed above the top positive electrode film, and a 6 μm copper foil is placed below the bottom negative electrode film. The stacked battery pack is placed in a hot press and held at 120 °C and 50 MPa for 10 minutes. Finally, the entire assembly is encapsulated in an aluminum-plastic film and heat-sealed to obtain an integrated battery cell with an internal series structure.
[0023] Comparative Example 1: Traditional bipolar battery with metal plate Cathode slurry preparation: 94 parts of lithium cobalt oxide cathode material, 3 parts of polyvinylidene fluoride binder, and 3 parts of conductive carbon black were dissolved in NMP solvent, and the cathode slurry was prepared by high-speed stirring and dispersion.
[0024] Negative electrode slurry preparation: 94 parts graphite negative electrode material, 3 parts polyvinylidene fluoride binder, and 3 parts conductive carbon black were dissolved in NMP solvent, and the negative electrode slurry was prepared by high-speed stirring and dispersion.
[0025] Bipolar plate unit fabrication: A 12 μm aluminum foil was used as the metal plate, and the front side of the aluminum foil was coated with a positive electrode paste with an areal density of 3.2 g / 100 cm³. 2 The reverse side of the aluminum foil is coated with a negative electrode paste with an areal density of 1.5 g / 100cm³. 2 The coated positive and negative electrode materials are dried and rolled to obtain a wet-processed bipolar plate unit.
[0026] Battery assembly: Refer to Figure 3 Four bipolar plate units are stacked, with a polyolefin separator placed between adjacent units. The cells are then encapsulated and heat-sealed using an aluminum-plastic film. Finally, electrolyte is injected and a vacuum is drawn to obtain a bipolar battery.
[0027] Comparative Example 2: A metal plate was added to Example 1. The preparation methods of the positive electrode self-supporting membrane, the negative electrode self-supporting membrane, and the separator are exactly the same as in Example 1.
[0028] The positive and negative self-supporting films are respectively hot-pressed onto both sides of a 12μm aluminum foil (each side of the aluminum foil is coated with a conductive carbon undercoat of about 2 μm thickness to improve contact), forming a three-layer composite structure of "positive film-aluminum foil-negative film".
[0029] Battery assembly: Four three-layer composite structural units are stacked alternately with a separator, i.e.: positive electrode film (composite on the front side of aluminum foil) / aluminum foil / negative electrode film (composite on the back side of aluminum foil) — separator — positive electrode film (composite on the front side of the next aluminum foil) / aluminum foil / negative electrode film (composite on the back side of the next aluminum foil) ... The outermost layer is provided with aluminum foil and copper foil terminals, and encapsulated with an aluminum-plastic film. The electrolyte and assembly conditions are the same as in Example 1.
[0030] Electrical performance comparison test: The discharge specific energy of the examples and comparative examples was tested at a 1C rate, and the results are as follows: Figure 4 As shown, the specific energy of the battery in this embodiment reaches 211.62 Wh / kg, while the specific energy of Comparative Example 1 is 166.58 Wh / kg and the specific energy of Comparative Example 2 is 171.54 Wh / kg. This indicates that the integrated metal-plate-free bipolar battery prepared using the patented technology has a specific energy increased by more than 20% compared to traditional bipolar batteries.
[0031] Rate testing was conducted on the examples and comparative examples at 1C, 2C, 5C, and 10C, respectively. The results are as follows: Figure 5 As shown. Example 1 has a specific energy of 145.54 Wh / kg at 10C, representing a 70.54% energy retention rate compared to 1C; Comparative Example 1 has a specific energy of 109.82 Wh / kg at 10C, representing a 66.91% energy retention rate compared to 1C; Comparative Example 2 has a specific energy of 114.84 Wh / kg at 10C, representing a 68.23% energy retention rate compared to 1C. In other words, the battery prepared using this patented technology has superior rate performance compared to traditional bipolar batteries.
[0032] The above description is merely a preferred embodiment of this application and does not limit the patent scope of this application. Any equivalent structural transformations made based on the inventive concept of this application and the contents of the specification and drawings of this application, or direct / indirect applications in other related technical fields, are included within the patent protection scope of this application.
Claims
1. A metal-plate-free bipolar solid-state battery, characterized in that, It includes at least two composite stacks stacked in series, each composite stack comprising a positive electrode self-supporting membrane, a separator, and a negative electrode self-supporting membrane stacked in series; in two adjacent composite stacks, the negative electrode self-supporting membrane of the previous composite stack is in contact with the positive electrode self-supporting membrane of the next composite stack.
2. The bipolar solid-state battery according to claim 1, characterized in that, The thickness of the positive electrode self-supporting membrane is 50~150μm, the thickness of the negative electrode self-supporting membrane is 40~120μm, and the thickness of the separator is 10~50μm.
3. The bipolar solid-state battery according to claim 2, characterized in that, According to the mass percentages of the raw materials, the positive electrode self-supporting membrane contains 60-90 parts of positive electrode active material, and the negative electrode self-supporting membrane contains 60-90 parts of negative electrode active material; and both the positive electrode self-supporting membrane and the negative electrode self-supporting membrane further contain: 5-25 parts of solid electrolyte powder, 2-10 parts of conductive agent, and 1-8 parts of binder.
4. The bipolar solid-state battery according to claim 3, characterized in that, According to the mass fractions, the diaphragm contains 85-98 parts of solid electrolyte powder and 2-15 parts of binder.
5. The bipolar solid-state battery according to claim 4, characterized in that, The positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, and lithium iron phosphate; The negative electrode active material is selected from one or more of synthetic graphite, natural graphite, hard carbon, soft carbon, silicon-carbon composite material, lithium titanate, and lithium metal. The solid electrolyte powder is selected from one or more of oxide electrolytes, sulfide electrolytes, and polymer electrolytes.
6. The bipolar solid-state battery according to claim 5, characterized in that, The conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene. The adhesive is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, or polyimide.
7. The method for preparing a bipolar solid-state battery according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. According to the above mass proportions, the raw materials are mixed separately and then rolled to form a positive electrode self-supporting membrane, a separator and a negative electrode self-supporting membrane of the target thickness. S2. The positive electrode self-supporting membrane, the separator and the negative electrode self-supporting membrane are stacked in sequence and hot-pressed to obtain a composite stack; at least two composite stacks are stacked and hot-pressed to obtain a fuel cell stack structure. S3. Place a positive electrode current collector above the top positive electrode self-supporting film of the stack structure, and place a negative electrode current collector below the bottom negative electrode self-supporting film. The whole package can be used to obtain a bipolar solid-state battery.
8. The preparation method according to claim 7, characterized in that, The hot pressing temperature is 80~200℃ and the pressure is 10~200 MPa.
9. The preparation method according to claim 8, characterized in that, The mixing process employs airflow milling or high-energy ball milling; the mixture is then repeatedly rolled using a roller press under room temperature or heating conditions.
10. The preparation method according to claim 9, characterized in that, The positive terminal subcurrent collector is an aluminum foil, and the negative terminal subcurrent collector is a copper foil.